Perturbing the ubiquitin pathway reveals how mitosis is hijacked to denucleate and regulate cell proliferation and differentiation in vivo. - Andrea Caceres; Fu Shang; Eric Wawrousek; Qing Liu; Orna Avidan; Ales Cvekl; Ying Yang; Aydin Haririnia; Andrew Storaska; David Fushman; Jer Kuszak; Edward Dudek; et al. (PLoS ONE)
Background The eye lens presents a unique opportunity to explore roles for specific molecules in cell proliferation, differentiation and development because cells remain in place throughout life and, like red blood cells and keratinocytes, they go through the most extreme differentiation, including removal of nuclei and cessation of protein synthesis. Ubiquitination controls many critical cellular processes, most of which require specific lysines on ubiquitin (Ub). Of the 7 lysines (K) least is known about effects of modification of K6. Methodology and principal findings We replaced K6 with tryptophan (W) because K6 is the most readily modified K and W is the most structurally similar residue to biotin. The backbone of K6W-Ub is indistinguishable from that of Wt-Ub. K6W-Ub is effectively conjugated and deconjugated but the conjugates are not degraded via the ubiquitin proteasome pathways (UPP). Expression of K6W-ubiquitin in the lens and lens cells results in accumulation of intracellular aggregates and also slows cell proliferation and the differentiation program, including expression of lens specific proteins, differentiation of epithelial cells into fibers, achieving proper fiber cell morphology, and removal of nuclei. The latter is critical for transparency, but the mechanism by which cell nuclei are removed has remained an age old enigma. This was also solved by expressing K6W-Ub. p27(kip), a UPP substrate accumulates in lenses which express K6W-Ub. This precludes phosphorylation of nuclear lamin by the mitotic kinase, a prerequisite for disassembly of the nuclear membrane. Thus the nucleus remains intact and DNAseIIβ neither gains entry to the nucleus nor degrades the DNA. These results could not be obtained using chemical proteasome inhibitors that cannot be directed to specific tissues. Conclusions and significance K6W-Ub provides a novel, genetic means to study functions of the UPP because it can be targeted to specific cells and tissues. A fully functional UPP is required to execute most stages of lens differentiation, specifically removal of cell nuclei. In the absence of a functional UPP, small aggregate prone, cataractous lenses are formed.